The mechanism of applying the value chain model and its impact on enhancing the effectiveness of the accounting information system: An applied study in the Iraqi Dates Manufacturing and Marketing Company (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to shed light on the method of value chain analysis and its role in enhancing the effectiveness of the accounting information system by showing the host and non-host activities of the value in the company, the research sample in order to exclude them, and to indicate the most important results possible to be obtained from the adoption of an advanced accounting information system that contributes to raising the efficiency of the company's performance by providing management with detailed information and future visions through which it is able to make decisions based on the analysis of the main and supporting activities, and in order to achieve the objectives of the study and verify the validity of its hypotheses, modern cost techniques have been adopted, and the industrial sector has been manufacturing and marketing The study concluded with a set of conclusions, the most important of which is the analysis of the value chain contributes to reducing costs by separating the activities and the host value statement and work to enhance them and exclude the costs of non-host value activities in order to increase the efficiency and effectiveness of the accounting information system at work, in addition, the study recommends raising the level of efficiency and skill of employees  thought activating training programs and specialized courses in the field of work in order to be able to deal with the advanced accounting information system and the mechanisms of applying the value chain, which contributes to improving their performance and in line with the continuous developments in business environment.